DEVELOPMENT AND IMPLEMENTATION OF THE PRESENTMED DIGITAL PLATFORM FOR END-TO-END PATIENT ROUTING IN COLOPROCTOLOGY - Matkarimov Sanjarbek Rahimboyevich; Abdusattarov Khurshid Abdusamatovich; Sa'dullayev Samariddin Ulug‘bek o‘g‘li (Western European Studies, 2025)
This study presents a pilot implementation of the PresentMed digital platform designed for end-to-end patient routing in coloproctology. The platform integrates outpatient, inpatient and telemedicine services into a unified digital ecosystem, enabling electronic medical records, standardized clinical pathways, remote consultations and real-time analytical monitoring. During implementation (630 patients across multiple regions of Uzbekistan), significant improvements were recorded, including reduced diagnostic delays, fewer uncoordinated referrals, increased use of telemedicine consultations and higher compliance with clinical protocols. Clinical outcomes also improved: rates of early diagnosis increased, access to advanced diagnostic procedures expanded and the need for surgical interventions was nearly halved. Patient satisfaction and treatment adherence demonstrated measurable growth. These findings confirm the effectiveness of the integrated digital model and highlight its potential for broader scaling within specialized care
Keywords: digital platform; patient routing; telemedicine